Ask Question
26 March, 03:52

Rewrite f (x) = - (x + 3) 2 - 1 from vertex form to standard form. f (x) = - x2 - 6x - 10 f (x) = x2 + 6x + 8 f (x) = x2 - 6x - 8 f (x) = x2 - 8

Answers (1)
  1. L
    26 March, 07:15
    0
    F (x) = - (x+3) ²-1

    f (x) = - (x²+6x+9) - 1

    f (x) = - x²-6x-10

    the first choice is correct.
Know the Answer?
Not Sure About the Answer?
Find an answer to your question ✅ “Rewrite f (x) = - (x + 3) 2 - 1 from vertex form to standard form. f (x) = - x2 - 6x - 10 f (x) = x2 + 6x + 8 f (x) = x2 - 6x - 8 f (x) = ...” in 📘 Mathematics if you're in doubt about the correctness of the answers or there's no answer, then try to use the smart search and find answers to the similar questions.
Search for Other Answers
Sign In
Ask Question